Himalayan Conifers as Important Source of Raw Material for Pulp and Paper Industry - Singh, R. V. (Indian Forester, 1970)
The raw material requiremtents of pulp and paper industry are expected to increase considerably in the near future. Adequate supply of long-fibred pulp wood is very necessary for the future expansion of pulp and paper industry as the utilisation of hardwoods potential is linked with the availability of long-fibred raw material. Long-fibred raw material is provided by the coniferous forests of Himalayas and the bamboo forests in many parts of the Country. This paper pleads for treating the Himalayan conifers as an important source of raw material for the pUlp and paper industry rather than relegating them as inaccessible and outside the limits of economic exploitation. It has also been brought out that conifers are capable of giving higher yield per unit area than bamboos and should therefore, be regarded as more important source of long-fibred raw material than bamboos.